Methylene blue reduces peritoneal adhesions in Syrian golden hamsters that undergo hepatopancreatic surgical procedures - Morioka, Cintia Yoko; Machado, Marcel Cerqueira Cesar; Otoch, Jose Pinhata; Saito, Seiji; Silva, Joelmir Lucena Veiga da; Watanabe, Akiharu; Arai, Hideki; Sakamoto, Takashi; Yamamoto, Keiichi; Figueiredo, Luiz Francisco Poli de (International Journal of Scientific Research and Management (IJSRM), 2021)
Tissue ischemia, mechanical or thermal trauma, infection and foreign body reaction predispose to adhesion formation. Adhesion formation resembles an inflammatory process. Sometimes, they appear as a bridge to wound healing, however, in other times it may cause small bowel obstruction. Methylene blue is known to inhibit the generation of oxygen radicals. Therefore, it may be used as an antioxidant reducing adhesion formation. Hamsters are animals used in surgical experiments, including pancreatic and hepatic surgeries. Objective. To study the effectiveness of using methylene blue in hamsters that undergo hepatectomy or pancreatectomy. Methods. Syrian golden hamsters were divided in 6 groups: Partial pancreatectomy with splenectomy (PPS), PPS and MB (PPS-MB), Partial hepatectomy (PH), PH and MB (PH-MB), Sham operation (SO), and Sham operation and MB (SO-MB). MB was administered intraperitoneally before closing abdominal wall. Side effects were observed. Animals were sacrificed 10 days later and adhesions were quantified. Results. Adhesions were present in all animals (100%) of PH group and 3 of 5 (60%) of PPS group. In PH-MB and SO groups, 1 of 5 hamsters (20%) in each group showed adhesions. No adhesions were found in PPS-MB and SO-MB treated groups. None of animals showed loss of weight. Conclusion. This study suggests that methylene blue administration showed to be effective to prevent adhesion formation in hepatopancreatic surgical procedures.